Reconstructing Meaning After Trauma 2017
DOI: 10.1016/b978-0-12-803015-8.00006-1
|View full text |Cite
|
Sign up to set email alerts
|

Spiritually Oriented Psychotherapy for Trauma and Meaning Making Among Ethnically Diverse Individuals in the United States

Abstract: Esmeralda, a 42-year-old Latina woman from Mexico, had moved to the Reconstructing Meaning After Trauma 98 there still remains more research and understanding needed to employ these strategies in the counseling session (Richards & Bergin, 2014). Additional training from experts and practitioners using these interventions with diverse populations in session would be helpful for psychotherapists who may want to incorporate spiritually oriented strategies with their clients. We hope that this chapter will stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 268 publications
0
6
0
Order By: Relevance
“…In many diverse groups in the United States, spirituality is deeply entrenched in the framework of their cultures. The unification of culture and spirituality is not only prominent but also inherently permeated in their way of being (Allen et al, 2017).…”
Section: How Do We Integrate Spirituality Into Psychotherapy?mentioning
confidence: 99%
“…In many diverse groups in the United States, spirituality is deeply entrenched in the framework of their cultures. The unification of culture and spirituality is not only prominent but also inherently permeated in their way of being (Allen et al, 2017).…”
Section: How Do We Integrate Spirituality Into Psychotherapy?mentioning
confidence: 99%
“…Since many survivors view their recovery process as a spiritual journey (Allen et al, 2017), it is probable that they will find meaning in spiritual frameworks and practices (Peres et al, 2007). Spirituality is described as a journey that leads the individual beyond themselves (Ronel, 2008) and toward a search for the Sublime (Pargament, 2007); it is evident in a person's attempts to identify their maladaptive patterns in a variety of situations, and accordingly to grow and alter their life for the better (Dambrun & Ricard, 2011).…”
Section: Spiritualitymentioning
confidence: 99%
“…This should come as no surprise, since survivors suffer from multifaceted implications, including physical, psychological (cognitive and emotional), social, and contextual (Prior & Petra, 2020; Sinko et al, 2022). Among those implications are a sense of powerlessness (Ronel, 2008), self-blame and guilt (Peter-Hagene & Ullman, 2018), anger and frustration (Allen et al, 2017), loss of trust (Lahav et al, 2020), tendency to revictimization (Brenner et al, 2021), and lack of social recognition (Kirkner & Ullman, 2020). Beyond disrupting psychosocial functioning, sexual trauma has all kinds of devastating implications on survivors’ spirituality, such as negative spiritual coping (i.e., spiritual discontent, fear of punishment, or blaming God for not being a protector), alienation from God, and loss of faith and meaning (Bryant-Davis & Wong, 2013; Walker et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…And, as social capital can be both increased or undermined, even before these concepts were described or there were scales to measure them, those belonging to powerful social groups have sought to destroy the social capital of subordinate communities. A wide variety of studies have demonstrated that social capital can be increased through community currency, social events or community architectural structures, 29,[31][32][33][34] while conversely, social capital can be damaged by things such as destroying community space. 35 Some marginalized communities use community coping mechanisms which are unique and adapted to the specific stresses faced by their societies.…”
Section: The Role Of Community In Copingmentioning
confidence: 99%
“…Oppression and marginalization can also injure a person's sense of spirituality and connection with the divine. With respect to meaning making after trauma, Allen et al 32 note that spiritual resources and interventions that are in line with a person's beliefs can help people cope, heal, and grow. Religious rituals can be used to enact destroying the traumatized life and nurture an experience of a renewed and more meaningful life.…”
Section: Some Therapeutic Best Practices For Minority Copingmentioning
confidence: 99%